Menikah Muda : Menggali Dampak Tersembunyi pada Pendidikan dan Karir - Agustina Tresendi Ndala; Wilfrida Chintia Teku; Yohanes Filkianus Malik; Wefrondi Leoh; Valentina Anjelin Rubu; Karolus T. Sius; Maria Florencia Yunita Bello (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Early marriage remains a serious problem in Indonesia, with a significant impact on the education and careers of the younger generation. This community service program aims to increase awareness about the impact of early marriage through outreach to students of SMA Negeri 1 Nagawutung, Lembata Regency. The method used is direct socialization by delivering material and interactive question and answer sessions. The results of research in Babokerong Village, Nagawutung District show that the factors causing early marriage include pregnancy outside of marriage, environmental influences, and exposure to mass media. The negative impacts of early marriage on education and career include dropping out of school, limited access to further education, decreased quality of learning, limited job opportunities, low income, and lack of economic independence. The socialization activity received a positive response from participants, with high enthusiasm in the question and answer session. In conclusion, a holistic approach is needed involving legal reform, educational intervention, economic empowerment, and changes in social norms to overcome the problem of early marriage and its impact on the education and careers of the younger generation